Kekerasan dalam Rumah Tangga dan Pendidikan untuk Pembinaan Moral Anak - Endang Danial Ar (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2007)
Domestic violence gives influence on students' morality. This study aims to describe students' knowledge of and attitudes toward domestic violence. The data collected from 250 students of primary schools, 150 of junior high school, and 100 of senior high schools indicate that domestic violence make children feel inferior, scared, lazy, and doubtful. When finding such violence, they would report it to neighbors, policeman, or relatives. Children's moral education can be developed in the family education basis